The key to love - St. Amant, Betsy (Revell, a division of Baker Publishing Group, 2020)
"The only thing Bri Duval loves more than baking is romance, so she creates a lovelock wall right outside her Parisian-style bakery in the middle of Kansas. When a love-scorned travel writer arrives in town, things start to heat up-in and out of the kitchen"--